2012
DOI: 10.1556/aoecon.62.2012.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure and its choice in Central and Eastern Europe

Abstract: We analyze the determinants of capital structure and its choice by small and medium-sized enterprises in Central and Eastern Europe from 2002 to 2007. We test the relevance of the three main theories: the Static Trade-off Theory, the Pecking Order Theory, and the Agency Theory, which have been derived primarily for developed markets, because our knowledge on their validity for emerging European countries is limited. We confirm the positive impact of size and asset tangibility on the leverage, while rejecting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 39 publications
4
20
1
Order By: Relevance
“…It is also compatible with the findings of most of the other studies. Bauer (2004), Nivorozhkin (2004), Berk (2007), Črnigoj and Mramor (2009), Avarmaa et al (2011), Kędzior (2012 are representative for the research stream covering the post-transition economies, but the results of Hernádi and Ormos (2012) and Jõeveer (2013) in the case of listed firms fail to support this.…”
Section: Resultsmentioning
confidence: 99%
“…It is also compatible with the findings of most of the other studies. Bauer (2004), Nivorozhkin (2004), Berk (2007), Črnigoj and Mramor (2009), Avarmaa et al (2011), Kędzior (2012 are representative for the research stream covering the post-transition economies, but the results of Hernádi and Ormos (2012) and Jõeveer (2013) in the case of listed firms fail to support this.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, SMEs are facing higher relative transaction costs than bigger companies in their issuance decisions. Numerous recent studies (see Berger and Udell, 1998, Berggren et al, 2000, Chittenden et al, 1996, Michaelas et al, 1999and Hernadi and Ormos, 2012 found the POT to be followed among SMEs. On the other hand, investigating this field by directly surveying financial executives in the US, Graham and Harvey (GH, 2001) perceive a pecking order-driven behavior among firms but conclude that this is not due to conventional POT factors such as size or growth, both of which should influence the implied informational asymmetry.…”
Section: Summary Of Recent Empirical Findingsmentioning
confidence: 97%
“…Empirically, certain results find that size of the firm has positive impacts on its leverage like the results of Titman & Wessels (1988); Rathinasamy, Krishnaswamy, & Mantripragada (2000); Huang & song (2006). In the other side negative relationship between size and leverage of the firm has been found by Rajan & Zingales (1995); Shah & Khan (2007); Hernádi & Ormos (2012).…”
Section: Firm Sizementioning
confidence: 87%